Coupling Compounds Behavior on Types of Fungi (American International Journal of Sciences and Engineering Research, 2019)
In  our  past  work , some   coupling  azo- compounds  were  formatted  characterized , chemical  identification   , which appeared  good  evidences  for  production  our  azo-coupling   compounds , while  in this  paper  , these  azo-coupling   derivatives  were   studied  against  types  of   fungi.